Features of vaginal microbiota in chronic cervicitis and chronic endometritis in women with miscarriage - I. N. Danusevich; Ya. G. Nadelyaeva; L. M. Lazareva; U. M. Nemchenko; L. I. Kolesnikova (Acta Biomedica Scientifica, 2025)
Background. Studying the microbiome in the conditions of a sluggish process and low-symptom clinical picture in women with miscarriage will help to understand the role of the microbial factor in the development of chronic inflammatory diseases of the pelvic organs (CIP). The aim. To study the composition of vaginal microbiota in chronic cervicitis and chronic endometritis to assess the scope of diagnostic examinations in case of miscarriage. Material and methods. The observational study involved 113 patients with miscarriage associated with chronic inflammatory diseases of the pelvic organs. The respondents filled out questionnaires, underwent general clinical, gynecological and instrumental examination. Evaluation of the microbiota of the vaginal contents included microbiological, molecular biological and bacteriological methods. Statistical analysis of the data was carried out using the Statistica 6.1 Statsoft Inc., USA program. Results. In all study groups, associations of microaerophiles with mycoplasma representatives were revealed (p > 0.05); obligate anaerobic and facultative anaerobic flora prevailed in patients with CE and CE with chronic cervicitis (ꭓ2 = 0.014, p < 0.05); HPV in association with obligate anaerobic and facultative anaerobic flora were observed in groups with chronic cervicitis (p < 0.001); herpesvirus infection was detected in groups with chronic cervicitis and CE with a predominance of CMV infection in patients with chronic endometritis (ꭓ2 = 0.045, p < 0.05), while the number of lactobacilli did not have significant differences. The species diversity of the vaginal biotope in chronic endometritis did not depend on the activity of plasma cells in the endometrium, the microbiota was detected in low non-pathogenic titers (102–104 CFU/ml). Conclusion. It is necessary to take into account the qualitative and quantitative composition of dysbiotic changes in the vaginal microbiota to improve the diagnosis of the etiological factor and justify an in-depth examination, including an assessment of the immune status, in order to improve the effectiveness of preventing miscarriage associated with chronic pelvic inflammatory disease.